Prevalence of upper-cross syndrome in college going students-a cross sectional study - P. V., Chithra; Vishwanath, Sneha (International Journal of Research in Medical Sciences, 2022)
Background: Upper cross syndrome is becoming more prevalent in today’s population. Upper crossed syndrome refers to overactive and underactive muscles group in the neck and shoulder girdle. Our aim in this study is to check the tightness and weakness of shoulder and scapular muscles. Methods: 100 adults with age group between 18-23 years were randomly selected for the study. All the students were selected based on inclusion and exclusion criteria. Tightness for pectoralis major, trapezius weakness and neck disability index (NDI) was measured. Data was analysed using SPSS version 20. Mean and SD was analyzed. Frequency was assessed with percentage. Results: Frequency of tightness of pectoralis major was 8% and weakness of trapezius was 59% respectively. NDI values with mean values 36.66 (30.89) was measured. Conclusions: Upper cross syndrome is found to be prevalent in college going students.